Kinetic study of the crystallization process of the α-Fe phase in the amorphous Fe81B13Si4C2 alloy - Janković, Bojan Ž. (Vojnotehnički glasnik / Military Technical Courier, 2013)
The kinetic study of the crystallization process of the α-Fe phase from the amorphous Fe81B13Si4C2 alloy was investigated by DSC and XRD techniques. The kinetic parameters (lnA, Ea) of the investigated process were determined using the Kissinger and isoconversional (model-free) methods. It was established that the α-Fe crystallization process can be described by the JMA (Johnson-Mehl-Avrami) kinetic equation. In accordance with the XRD analysis and the calculated crystallization parameters (n = 4; m = 3), it was concluded that the crystallization stages of the considered process can be described by the bulk nucleation and the three-dimensional (3D) growth of nuclei.
Keywords: crystallization; amorphous alloys; kinetic analysis; apparent activation energy; XRD; DSC